2019
DOI: 10.1007/s00429-019-01976-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity and functional properties of the macaque superior parietal lobule

Abstract: Despite the consolidated belief that the macaque superior parietal lobule (SPL) is entirely occupied by Brodmann's area 5, recent data show that macaque SPL also hosts a large cortical region with structural and functional features similar to that of Brodmann's area 7. According to these data, the anterior part of SPL is occupied by a somatosensory-dominated cortical region that hosts three architectural and functional distinct regions (PE, PEci, PEip), and the caudal half of SPL by a bimodal somato-visual reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 139 publications
(207 reference statements)
8
60
0
Order By: Relevance
“…According to the studies from Lewis and Van Essen, 2000a and Bakola, Passarelli ( Bakola et al, 2017 ), three areas occupied the medial wall of the IPS: area PO is located in the junction with POS, and the remaining rostral part consists of two distinct areas. The middle area was named MIP ( Lewis and Van Essen, 2000a ; Bakola et al, 2017 ), whereas the rostralmost area was identified as area 5V ( Lewis and Van Essen, 2000a ) or as area PEip ( Bakola et al, 2017 ; Gamberini et al, 2020a ). The present partitioning scheme was able to confirm the existence of these two areas, their location and extent are more similar to the scheme charted by Bakola et al, 2017 , so we followed their nomenclature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the studies from Lewis and Van Essen, 2000a and Bakola, Passarelli ( Bakola et al, 2017 ), three areas occupied the medial wall of the IPS: area PO is located in the junction with POS, and the remaining rostral part consists of two distinct areas. The middle area was named MIP ( Lewis and Van Essen, 2000a ; Bakola et al, 2017 ), whereas the rostralmost area was identified as area 5V ( Lewis and Van Essen, 2000a ) or as area PEip ( Bakola et al, 2017 ; Gamberini et al, 2020a ). The present partitioning scheme was able to confirm the existence of these two areas, their location and extent are more similar to the scheme charted by Bakola et al, 2017 , so we followed their nomenclature.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this shift in functional systems, from a caudo-lateral visual domain to a rostro-medial sensorimotor domain ( Grefkes and Fink, 2005 ; Lewis and Van Essen, 2000b ; Gamberini et al, 2020a ; Guipponi et al, 2013 ), is also the most significant trend reflected by changes in the shape and/or size of the fingerprints. From an overall perspective, the rostralmost areas (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Like the macaque VIP, area NCP1 is located posterior to a region of visual tactile convergence ( Figure 2B [33]). This region may correspond to area 5 [40], which in monkeys hosts neurons involved in the sensorimotor control of limb action [41], including numerosity [25,26].…”
Section: Numerosity and Action In The Human Brainmentioning
confidence: 99%
“…The associative cortices, like the posterior parietal cortex (PPC), include a variety of multimodal associative areas whose neurons are modulated by a plethora of different factors ( Binkofski and Buccino, 2018 , Galletti and Fattori, 2018 , Gamberini et al., 2020 ). Within macaque PPC area V6A, located in the anterior bank of parieto-occipital sulcus, ( Galletti et al., 1999 ), is a higher-order visuomotor area modulated by visual signals coming from the whole visual field and somatic signals coming from the upper limbs ( Gamberini et al., 2011 , 2018 ), as well as by oculomotor signals related to gaze position and eye movement ( Galletti et al., 1995 ; Kutz et al., 2003 Breveglieri et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%